2019
DOI: 10.4103/ijmr.ijmr_290_18
|View full text |Cite
|
Sign up to set email alerts
|

Targeted sequencing of the DMD locus: A comprehensive diagnostic tool for all mutations

Abstract: Background & objectives:Duchenne muscular dystrophy (DMD) is an X-linked recessive disorder and is caused mainly by deletion, duplication and point mutations in the DMD gene. Diagnosis of DMD has been a challenge as the mutations in the DMD gene are heterogeneous and require more than one diagnostic strategy for the validation of the mutation. This study was planned to evaluate the targeted next-generation sequencing (NGS) as a single platform to detect all types of mutations in the DMD gene, thereby reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Previously, many studies have been published for NGS-based approaches for MD ( Lim et al, 2011 ; Wang et al, 2014 ; Wei et al, 2014 ; Alame et al, 2016 ). However, there are very few such studies reported for the Indian population ( Aravind et al, 2019 ; Ganapathy et al, 2019 ; Polavarapu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, many studies have been published for NGS-based approaches for MD ( Lim et al, 2011 ; Wang et al, 2014 ; Wei et al, 2014 ; Alame et al, 2016 ). However, there are very few such studies reported for the Indian population ( Aravind et al, 2019 ; Ganapathy et al, 2019 ; Polavarapu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the NGS platforms also identified the novel variants as well as confirmation of hard-to-detect variants ( Sheikh and Yokota, 2020 ). Recent studies suggest that the utilization of a high-throughput method using NGS platform is more suitable for clinical diagnosis ( Okubo et al, 2016 ; Aravind et al, 2019 ). Moreover, the detection of large duplications is a major challenge for single-point diagnostic strategy ( Okubo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic genetic tests, on the other hand, help in identification of the molecular cause of the disease. These tests are used to confirm known or suspected diagnosis, carrier status determination, identification of at-risk genetic relatives, optimize treatments, and clinical decisions (Gupta et al, 2017;Aravind et al, 2019;Uttarilli et al, 2019). There are different types of diagnostic genetic tests currently available in India such as single-gene and multigene testing, exome, and genome sequencing, carrier and newborn screening (Puri et al, 2017;Singh et al, 2018).…”
Section: Current State Of Genetic Testingmentioning
confidence: 99%
“…The severity of DMD depends on the mutation type. ‘Out of frame’ mutations disrupt the reading frame and further produce the dysfunctional dystrophin, which result in the severe DMD phenotype ( Aravind et al, 2019 ). On the other hand, ‘In-frame’ mutations perverse the frame of DMD gene and generate partial functional dystrophin protein, which lead to less severe Becker muscular dystrophy (BMD) phenotype ( Haidet et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%